A Novel Method of Impeller Blade Monitoring Using Shaft Vibration Signal Processing - Liska, Jindrich; Vasicek, Vojtech; Jakl, Jan (Sensors (Basel, Switzerland), 2022)
The monitoring of impeller blade vibrations is an important task in the diagnosis of turbomachinery, especially in terms of steam turbines. Early detection of potential faults is the key to avoid the risk of turbine unexpected outages and to minimize profit loss. One of the ways to achieve this is long-term monitoring. However, existing monitoring systems for impeller blade long-term monitoring are quite expensive and also require special sensors to be installed. It is even common that the impeller blades are not monitored at all. In recent years, the authors of this paper developed a new method of impeller blade monitoring that is based on relative shaft vibration signal measurement and analysis. In this case, sensors that are already standardly installed in the bearing pedestal are used. This is a significant change in the accessibility of blade monitoring for a steam turbine operator in terms of expenditures. This article describes the developed algorithm for the relative shaft vibration signal analysis that is designed to run in a long-term perspective as a part of a remote monitoring system to track the natural blade frequency and its amplitude automatically.
Keywords: pára; Vibration; algoritmy; monitoring; chirurgické nástroje; Surgical Instruments; signal processing; Signal Processing, Computer-Assisted; algorithm; diagnostics; vibration; steam turbine; počítačové zpracování signálu; vibrace; Steam; impeller blade; Algorithms